Aerobic and facultative anaerobic Klebsiella pneumoniae strains establish mutual competition and jointly promote Musca domestica development - Zhang, Kexin; Wang, Shumin; Yao, Dawei; Zhang, Xinyu; Zhang, Qian; Liu, Wenjuan; Li, Ying; Yin, Yansong; An, Sha; Zhang, Ruiling; Zhang, Zhong (Frontiers in Immunology, 2023)
The housefly gut contains a rich and diverse microbial community that plays crucial roles in larval development. However, the impact of the lack of specific symbiotic bacteria on larval life activities and the composition of the housefly natural gut microbiota remain unclear. In this study, the aerobic bacterium Klebsiella pneumoniae KX and the facultative anaerobic bacterium K. pneumoniae KY were isolated from intestinal tracts of housefly larvae. The K. pneumoniae KX/KY-specific bacteriophages KXP/KYP were used as an accurate tool to analyse the effects of K. pneumoniae on larval development. Our results showed that individual supplementation of K. pneumoniae KX and KY in larval diets could both promote larval growth, while mixed feeding of the two bacteria had no significant synergistic effect. High-throughput gene sequencing results showed that bacterial abundance of Klebsiella increased while those of Provincia, Serratia and Morganella decreased when larvae were fed a K. pneumoniae KX, KY and KX-KY mixture. K. pneumoniae KX/KY both inhibited the growth of Pseudomonas and Providencia. When the bacterial abundance of both strains increases at the same time, it will reach a balance in the total bacterial abundance. We assume that aerobic K. pneumoniae KX and facultative anaerobic K. pneumoniae KY maintain a mutual balance to facilitate common development in the intestines of houseflies, not only competing but also cooperating with each other to maintain the steady state of the intestinal bacteria of housefly larvae. Our results highlight the important role of K. pneumoniae in shaping the normal gut microbiota composition in insects.